Extraction mechanism of ferric and manganese ions with aqueous two-phase system formed by ionic liquid and polyethylene glycol - Ola, Pius Dore (Array, 2019)
In this work, we employed an aqueous two-phase system formed by an ionic liquid and polyethylene glycol for the separation of Fe(III), which is the most commonly used metal in the world, and Mn(II), which is currently used in many industries. We found that the extraction mechanisms of Fe(III) and Mn(II) were strongly influenced by the concentration of the hydrochloric acid that dissolved the metal salt. The ion pair reaction was the predominant mechanism that generated the Fe(III) and Mn(II) extractions. At a lower concentration of hydrochloric acid, metal ions were extracted because of the reaction between a metal cation and a dodecylsulfonate anion. At a higher concentration of hydrochloric acid, the reaction between a metal chlorocomplex anion and a hexylmethylimidazolium cation also proceeded. The aqueous two-phase system, composed of ionic liquid and polyethylene glycol, is promising for metal separation based on the difference in the affinity of metal with alkyl-sulfonate in a low HCl concentration and in the stability constant of metal chlorocomplex in a high HCl concentration. The maximum extractability of Fe(III) and Mn(III) was 57.8 and 75.3 %, respectively, with 0.3 mol dm–3 hydrochloric acid concentration.